Gambaran Perilaku Remaja Putri Pada Masa Pubertas Di Desa Tanjungrejo Grobogan - Prabawani, Cahya Rida; , Siti Arifah,S. Kp., M. Kes; , Endang Zulaicha S, S.Kp., M.Kep (2016)
Puberty refers to when there is a reproductive ability, maturation of the reproductive organs is characterized by menstruation in girls. At the time problems arise due to changes in the physical and hormonal changes cause anxiety, denial and shame, the nature of these perceptions shape behavior. This study aims to know the description of the behavior of teenage girls at puberty in the village Tanjungrejo Grobogan. This research is descriptive exploratory study. Samples were 76 girls who have experienced menstruation in the village Tanjungrejo Grobogan. Results of the study are: (1) Feelings of young women in the face of first menstruation is feeling sad, embarrassed, anxious, worried, confused and afraid. The first person who told the mother, the culture surrounding menstruation is not to be washed when menstruating, use sanitary napkins to show all young women use sanitary napkins modern, behavior of adolescent girls against former bandage that has been used is to remove the bandage by first washing, wrapping and discarded in the trash , the amount of use of sanitary napkins pads 3 pieces a day, (2) The behavior of young women in the face of menstrual pain is to use pain relief medications that are sold freely in stores. (3) The behavior of young women in the face of acne showed mostly using acne medications that are sold freely in stores (4) The behavior of young women in the face of body odor is mostly teenage girls use deodorant (5) The behavior of young women in the face of changes in body shape shows some large felt like shape Penelitian ini adalah penelitian descriptive eksploratif. Sampel penelitian adalah 76 Remaja Putri yang sudah mengalami menstruasi di Desa Tanjungrejo Kabupaten Grobogan. Hasil penelitian adalah: (1) Perasaan remaja putri dalam menghadapi menstruasi pertama kali adalah merasa sedih, malu, gelisah, khawatir, bingung dan takut. Orang pertama yang diberitahu adalah ibu, budaya seputar menstruasi adalah tidak boleh keramas ketika menstruasi, penggunaan pembalut menunjukan semua remaja putri menggunakan pembalut modern, perilaku remaja putri terhadap bekas pembalut yang telah digunakan adalah membuang pembalut dengan terlebih dahulu mencuci, membungkus dan dibuang di tempat sampah, jumlah penggunaan pembalut sebanyak 3 buah pembalut sehari, (2) Perilaku remaja putri dalam menghadapi nyeri haid adalah menggunakan obat-obatan pereda nyeri yang dijual bebas di toko. (3) Perilaku remaja putri dalam menghadapi jerawat menunjukkan sebagian besar menggunakan obat jerawat yang dijual bebas di toko (4) Perilaku remaja putri dalam menghadapi bau badan adalah sebagian besar remaja putri menggunakan deodorant (5) Perilaku remaja putri dalam menghadapi perubahan bentuk tubuh menunjukkan sebagian besar merasa tidak menyukai bentuk tubuhnya.